Українські професійні об’єднання педагогів Галичини та Буковини (друга половина ХІХ – початок ХХ ст.): спроба порівняльного аналізу. - Dobrzhanskyi, Oleksandr; Шологон, Лілія (Кишинів, Молдова, 2022)
Abstract Focusing on the professional teachers’ associations of Galicia and Bukovyna, the author makes an attempt of comparative analysis and introduces a number of previously unknown sources to discuss six professional pedagogical associations established during the 1880s – early 20th century. The problems of public schools and proper professional level of their teachers came in sight of “Rus Pedagogical Society” (“Ukrainian Pedagogical Society”) in Galicia and the “Ruska Shkola” (“Ukrainian school”) 134 2022. № 68 in Bukovyna. “Mutual Aid of Ukrainian Teachers” and “Free Organization of Ukrainian Teachers in Bukovyna” defended the professional interests of school teachers respectively. Higher professional level of gymnasium teachers in Ukraine became a priority in the activities of the “Teachers’ Community” and the Hryhoriy Skovoroda Society of Higher School Teachers established in Lviv and Chernivtsi. Since Galicia and Bukovyna were separate autonomous regions within Austria-Hungary, they had their own teachers’ associations with the similar mission. The difficulties faced by the schools of these two regions were similar; however, they tackled them differently due to the specific political circumstances. As a result, the Ukrainian Pedagogical Society in Galicia had the most significant achievements in the creation of the Ukrainian-language primary schools, gymnasiums, teachers’ seminaries, courses for the illiterate and publishing activity, while the pedagogical assiciations of Bukovyna managed to protect the professional rights of teachers and achieve a significant increase in teachers’ salaries supported by other public associations and political parties of the region.
Keywords: товариство; професійні об’єднання педагогів; Галичина; Буковина; Австро-Угорська монархія; народні школи; «Руське товариство педагогічне» («Українське педагогічне товариство»; «Руська школа» («Українська школа")